An Introduction to Positive Organisational Scholarship in South Asia - James, Nisa; Victor, Vijay; George, Roji (Jurnal Organisasi dan Manajemen, 2020)
This study aims at creating an ensemble of the various principles of positive organizational scholarship professed in south Asia through ages. This is a review of various scholarly literature published between 1985 and 2020, on how positive organizational scholarship finds its roots in South Asia. Findings. Based on the detailed literature review, it was observed that south Asia has a distinct and rich spiritual culture which has given birth to many positive organisations. Positivity found in these indigenous organisations is strongly rooted in the concept of community development. It is also found that as compared to the western culture, the South Asian culture has been blessed with conscience of spirituality and this culture is capable of leading the entire world to peace, prosperity, and happiness. This study can be viewed as one of the pioneering attempts examining the roots of positive organizational scholarship in South Asia. This paper adds value to the body of existing knowledge by providing new insights into the virtues contributed by South Asia towards POS.